МетодологічнІ підходи до створення ГІС режиму ґрунтової вологи на основі агрогідрометеорологічного методу - Коваленко, Володимир Васильович; Kovalenko, Vlаdіmyr; Довганенко, Д. О.; Dovhanenko, D.; Білоброва, А. С.; Bilobrova, A. (Дніпровський державний аграрно-економічний університет, 2016)
Представлена методологія створення геоінформаційної системи режиму ґрунтової вологи, в основу якої покладено агрогідрометеорологічний метод розрахунку вологозапасів (АГММРВ), на прикладі озимої пшениці в умовах Дніпропетровської області. ГІС режиму ґрунтової вологи базується на встановленні логікостатистичної залежності між емпіричними параметрами АГММРВ, цифровою моделлю рельєфу, ґрунтовим покривом та погодними умовами. The paper deals with modernization of the agrarian and meteorological method of soil moisture content calculation (AMMSMCC) in the fields planted with the main agronomic cultures using weather information portal www.rp5.ua as base to developed GIS of the soil moisture regime. The optimized complex parameter of antecedent weather conditions calculated using open web-meteorological data base and accuracy of the method. The correlation between calculated and measured data is varying between 0,92 and 0,97 within upper 1 m soil layer and 0,9–0,94 – for half meter soil layer. Comparing with basic model the standard deviation is decries all over on 17–31 %. This level of accuracy allows to developed GIS of the soil moisture base on AMMSMCC. It was established that morphology is the main factor that has height level of affecting on precipitation distribution with in soil through infiltration, evaporation and regulation of the surface and subsurface runoff. Methodological approaches that formalized elevation and the soil cover as domain conditions of the soil moisture regime and its space inhomogeneity was developed. The formalization procedure is based on combination of the slope curvature, aspect, topographic wetness index, soil grain-size distribution and infiltration. The GIS algoritm of analysis of the soil moisture accumulation within agrarian cultures is developed. The logical and the statistical correlation between empirical data of the AMMSMCC, digital elevation model and soil cover features is established.Maps that was built in GIS allows to solve the problems of rational usage the agriculturally used areas, to estimate the hydrothermal inhomogeneity of slopes with different aspect and curvature; GIS of the soil moisture can be advanced in the soil monitoring system, adaptive soil management, precision agriculture, site class determination and land monetary value.
Methodological approach of developing GIS of the soil moisture regime based on the agrarian and meteorological method
Keywords: ґрунтова волога; soil moisture; агрогідрометеорологічний метод розрахунку вологозапасів; the agrarian and meteorological method; ГІС режиму вологи; GIS of the soil moisture regime